Geometry and Kinematics of Bivergent Extension in the Southern Cycladic Archipelago: Constraining an Extensional Hinge Zone on Sikinos Island, Aegean Sea, Greece. Issue 6 (7th June 2021) - Ring, Uwe; Glodny, Johannes
Abstract: We report the results of a field study on Sikinos Island in the Aegean extensional province of Greece and propose a hinge zone controlling incipient bivergent extension in the southern Cyclades. A first deformation event led to top‐S thrusting of the Cycladic Blueschist Unit (CBU) onto the Cycladic basement in the Oligocene. The mean kinematic vorticity number ( W m ) during this event is between 0.56 and 0.63 in the CBU, and 0.72 to 0.84 in the basement, indicating general‐shear deformation with about equal components of pure and simple shear. The strain geometry was close to plane strain. Subsequent lower‐greenschist‐facies extensional shearing was also by general‐shear deformation; however, the pure‐shear component was distinctly greater ( W m  = 0.3–0.41). The degree of subvertical pure‐shear flattening increases structurally upward and explains alternating top‐N and top‐S shear senses over large parts of the island. Along with an increased coaxial deformation component, the strain geometry became oblate. Published quantitative data from nearby Ios Island are similar and both data sets define an extensional hinge zone between top‐N extensional deformation across large parts of the central and northern Cyclades and top‐S extensional deformation at the southern and western fringe of the archipelago. This extensional hinge zone is an important large‐scale structure forming early in the history of lithospheric extension due to southward retreat of the Hellenic slab. Plain Language Summary: The Aegean Sea in the eastern Mediterranean is a largely land‐locked basin resulting from the southward retreat of the Hellenic subducting slab. The geometry of the extensional structures is debated. Our work on Sikinos Island and a comparison with structures from nearby Ios Island at the southern end of the Cycladic archipelago in the central Aegean extensional province suggests the existence of an extensional hinge zone of a bivergent extensional fault system. To the north of this symmetric hinge, the extensional faults are asymmetrically top‐N displacing, whereas to its south the extensional faults are top‐S displacing. The extensional hinge zone is an important large‐scale structure in the central Aegean Sea and might have an equivalent in West Turkey. We favor a model in which the symmetric hinge formed early during lithospheric extension, moved southward in concert with the retreating Hellenic slab, and then monovergent top‐N extensional faults formed in due course to the north of the extensional hinge Key Points: New and novel (re)interpretation of extension‐related structures in Cycladic Blueschist Unit Extensional structures resulted from high degree of pure‐shear flattening during general‐shear deformation Structures are interpreted to reflect an extensional hinge zone in southern Cyclades